PENERAPAN KOMPRES HANGAT UNTUK MENGURANGI NYERI PERSALINAN PADA NY R DI PUSKESMAS TANJUNG BALAI KARIMUN: PENERAPAN KOMPRES HANGAT UNTUK MENGURANGI NYERI PERSALINAN PADA NY R DI PUSKESMAS TANJUNG BALAI KARIMUN - Triana, Beril; Mona, Silvia (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
Maternity mothers who have difficulty adapting to labor pain can cause uncoordinated uterine contractions (reducing the ability of the uterus to contract) which can result in prolonging labor time. Labor pain is a condition in the form of an unpleasant feeling, if not handled properly it will cause other problems, namely increasing anxiety. Compresses are usually able to control pain, also provide a sense of comfort as well as relieve tension. The goal is to provide midwifery care for mothers in a comprehensive and continuous manner, with management of midwifery care in accordance with midwifery service standards. The midwifery care that is applied is the Application of Warm Compresses to Reduce Labor Pain in Mrs. R. The practice report preparation method is descriptive research using the case study method, carried out at the Tanjung Balai Karimun Health Center in March 2023 Results and Conclusions Evaluation of the care provided related to the implementation warm compresses to reduce labor pain there is a reduction in the pain that the mother feels